Monitoramento hidrológico transfronteiriço da Bacia Amazônica por altimetria espacial - Oliveira, Bernardo Luiz Ferreira de (2018)
The main objective of this study was to monitor the variation in water levels of the Amazon basin outside Brazilian territory, providing information complementary to the Amazon Hydrological Monitoring Bulletin Western. Monitoring was carried out by means of spatial altimetry, more specifically with the data generated by the Jason 2 and 3 altimetric missions. The altimetric data were validated, using as reference the serious historical four stations located near the projection of the satellite's orbit and within the Amazon basin and after this analysis, two Virtual Stations of Cross-border monitoring, one located on the Amazon River channel in Peru and another on the channel of the Negro River in Venezuela. These stations were inserted in a new model for the Hydrological Monitoring Bulletin of the Western Amazon.